2014
DOI: 10.1186/1471-2253-14-108
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of locating the cricothyroid membrane by palpation – an intergender study

Abstract: BackgroundThe cricothyroid membrane (CTM) is the recommended site of access to the airway during cricothyrotomy to provide emergency oxygenation. We sought to compare the ability of physicians to correctly identify the CTM in male and female patients.MethodsIn a prospective observational study, anaesthetists were asked to locate the CTM by palpation which was then identified using ultrasound and the distance between the actual and estimated margin of the CTM was measured. Participants assessed the ease of CTM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 28 publications
0
39
1
1
Order By: Relevance
“…Identification of landmarks in female patients had been reported to be more difficult irrespective of how high their BMI was found to be at the time of the procedure,10but this was not confirmed in our study. The previous study was done by anaesthesia physicians who had higher level of training in this procedure, while ED clinicians comprise of a more pragmatic population who are likely to encounter the need for securing a surgical airway.…”
Section: Discussioncontrasting
confidence: 83%
“…Identification of landmarks in female patients had been reported to be more difficult irrespective of how high their BMI was found to be at the time of the procedure,10but this was not confirmed in our study. The previous study was done by anaesthesia physicians who had higher level of training in this procedure, while ED clinicians comprise of a more pragmatic population who are likely to encounter the need for securing a surgical airway.…”
Section: Discussioncontrasting
confidence: 83%
“…Firstly, some authors have recommended marking the cricothyroid membrane (CTM) before induction of general anaesthesia if difficulty is anticipated [2,3], thus avoiding the need to identify the membrane for the first time during an unfolding emergency. Although this seems to make sense, these authors have suggested marking the CTM in the neutral or intubating position.…”
Section: Introductionmentioning
confidence: 99%
“…Palpation of cricothyroid membrane is limited by factors like thick pad of subcutaneous tissue, obesity and in females due to the relatively less palpable thyroid prominence. Palpation is also limited by distorted anatomy due to previous radiotherapy to neck and tracheal deviation [5]. A computed tomography (CT)-guided study demonstrated that cricothyroid membrane is not necessarily a superficial structure and also the smallest dimensions of the membrane may necessitate the use of smaller than recommended trocar and endotracheal tubes [6].…”
Section: Discussionmentioning
confidence: 99%